Essays on the economics of irrigation efficiency and carbon markets - Cameron Harp, Micah Vollmer (Kansas State University, 2022)
Essay 1 - Efficiency and water use: Dynamic effects of irrigation technology adoption. With the United States preparing to make a historic investment in drought mitigation, clarifying the impact of irrigation efficiency improvements on water resources is critically important. This paper uses three transitions in irrigation technology to investigate whether rebound effects cause such efficiency improvements to increase resource extraction, a phenomenon known as Jevon’s paradox. We demonstrate how staggered adoption of irrigation technologies and dynamic treatment effects can cause improperly specified two-way fixed effects (TWFE) estimates to falsely indicate that technology adoption increases withdrawals. Using estimators appropriate for these circumstances, we find no significant evidence of rebound effects causing Jevon’s paradox. The significant, dynamic effects we find explain this discrepancy and, perhaps more importantly, reveal irrigators’ process of adaptation to each new technology at the intensive and extensive margins. Essay 2 – Where will the United States farm carbon? Geographic variation in the profitability and carbon sequestration potential of conservation agriculture practices will determine how cost-effective agricultural carbon credit programs are across the United States. As data on agricultural carbon credit program enrollment are unavailable, we use county-level data on the rate of adoption of conservation agriculture practices as a proxy for the profitability of the practices. We then map the predicted rates of adoption with spatially explicit carbon sequestration data for two practices and predict how the cost efficiency of agricultural carbon credit programs will vary spatially in the United States. Essay 3 – Compensation mechanism, program scale, and the efficiency of voluntary carbon offset programs. In the present voluntary market for agricultural carbon credits, the fine scale nature of participation and evaluation can inhibit program administrators’ efforts to predict producers’ counterfactual behavior in the absence of a program and mitigate adverse selection. In addition, the uncertainty in estimates of soil carbon sequestration, the outcome used to issue carbon credits, increases rapidly as the scale of analysis decreases. Scaling up carbon farming programs to a jurisdiction level could address these issues by reducing uncertainty in both estimates, increasing the efficiency of achieving societal carbon sequestration goals. In such a jurisdictional approach to carbon farming programs, the program provides payments to jurisdictions based on the aggregate outcome of all producers within a jurisdiction. In this paper, we use a simulation approach to investigate the success of carbon farming programs with two different compensation mechanisms as a function of the program scale and design. When operating at the individual scale, we find programs using a per unit payment-for-sequestration approach are more efficient than those using a constant payment-per-practice mechanism only if the program administrator can estimate producers’ carbon sequestration potential with sufficient accuracy. As the uncertainty in carbon sequestration rises, the payment-for-practice program becomes more efficient in terms of the average cost of an additional unit sequestered. Finally, increasing the scale of the program improves the efficiency of the payment-for-practice program to a greater degree such that it can be more efficient than the alternative, even if the error in estimating carbon sequestration is low.
Keywords: Agricultural economics; Water; Carbon markets; Irrigation; Resource economics; Econometrics